Evaluation of seismic displacement demand for unreinforced masonry shear walls. Issue 1 (1st January 2018) - Vemuri, Jayaprakash; Ehteshamuddin, Syed; V. L. Kolluru, Subramaniam
Abstract: Unreinforced, non-engineered low-strength brick masonry structures comprise a large percentage of buildings in the Himalayan region and have been extensively damaged in recent earthquakes. Due to the high seismic hazard of the region and the inherent vulnerability of non-engineered masonry structures, a seismic assessment of masonry construction in this region is imperative. In this study, a suite of strong ground motions is developed using data from major Himalayan earthquakes. Using a mechanistic-based procedure for predicting the monotonic load envelope which identifies limit states of cracking, strength, and collapse using stress-based criteria, a hysteretic model was calibrated to experimental data of unreinforced masonry shear walls. Nonlinear time history analyses are performed on the validated single degree of freedom models of two unreinforced masonry walls. The analytical results correlate well with observed damage to masonry structures in Himalayan earthquakes. Peak ground acceleration of ground motion is observed to be the key parameter influencing displacement of walls. A linearly increasing trend is observed between the PGA and the observed displacement up to a PGA value of 0.1g. A weak correlation is observed between displacement and ground motion frequency parameters.